Rupturas y transformaciones arquitectónicas : Colegio Mayor de Nuestra Señora del Rosario de Bogotá, siglo XX - Paláu Rivas-Sacconi, Fernando; Restrepo Zapata, Jaime (Cuadernos para la historia del Colegio Mayor de Nuestra Señora del Rosario, 2018)
This monograph describes, analyzes and documents graphically and textually the architectural transformations carried out during the 20th century to the colonial cloister erected in Santa Fe de Bogotá (Colombia) by Fray Cristóbal de Torres in 1653 for the headquarters of the Colegio Mayor de Nuestra Señora del Rosario (currently Universidad del Rosario). The main transformations of 1900 are also analyzed, previous historical and academic context.